Study on hydrogen-induced stress corrosion of 7N01-T4 aluminum alloy for railway vehicles - Zhang Li-jiao; Li Ming-gao (High Temperature Materials and Processes, 2022)
7N01-T4 aluminum alloy is widely applied to high speed train body material attributed to its excellent comprehensive mechanical properties; however, its high sensitivity to hydrogen stress corrosion would seriously restrict its further application. In this study, the hydrogen-induced stress corrosion of the base metal and the joint was investigated under slow strain rate test to ascertain the characteristics and mechanism of hydrogen-induced stress corrosion cracking of aluminum alloy. By applying the cathode potential, the morphology of tensile port was studied. Results show that under the action of tensile stress, the free atomic hydrogen produced in the corrosion process or absorbed hydrogen diffuses along the grain boundary into the crack tip region, weakens the grain boundary and causes hydrogen embrittlement, thus accelerating the crack propagation and fracture. These properties provide a broader prospect for the application of 7N01-T4 aluminum alloy in high-speed train body.